The Rise and Development of Madrasas in Indonesia - Sarifah, Sarifah; Kadarusman, Haris; Warisno, Andi; Andari, An An; Anshori, M Afif (Graduate Program Magister Manajemen Pendidikan, 2023)
Madrasa is an educational institution that has gone through a long process as an educational institution. The emergence of madrasas as higher education institutions after non-formal educational institutions in previous times was due to the expansion of Islamic areas and the development of science which resulted in the consideration of these educational institutions as Islamic educational institutions which were no longer considered capable and adequate for the continuity of Islamic education. especially for those who wish to continue on to higher education. The emergence of the Nizhamiyah madrasah was basically a reaction to the development of Shi’ah understanding at that time, which began in the fourth century. This understanding seems to have developed so rapidly in many Islamic areas that were promoted by the Fatimid dynasty in Egypt. Bearing in mind that it was not enough to fight Shi’ah with force of arms, the government at that time fortified society from Shi’ah influence through education. So since then, madrasas have begun to develop institutionally and autonomously from various regions and develop as a whole as institutions that are sovereign in the power of Islamic political elites as purification of Islamic teachings from an early age and are legally institutionalized.